Evaluación de mecanismos de pago por servicios ambientales en la provincia de Loja y su relación con los Planes de Desarrollo Local - Moreno Fierro, Ivonne Esperanza (2015)
Examples of financial and legal mechanisms to promote conservation and payment mechanisms for environmental services PES incentives are relatively new instruments, is building up experience in many parts of the world, experience tells us that can only operate with good governance based on systems: political, legislative, economic, technical, environmental, cultural and institutional effective. In addition, specific rules to be applied worldwide is almost impossible, as the social, environmental, economic, legal and institutional framework of each country and even each locality context, should always be reflected in establishing such instruments. The overall objective of this research is to support the valuation of ecosystem services to be considered in the management plans of the autonomous governments of the Province of Loja; for this, two specific objectives are proposed: assessing initiatives payment for environmental services in the Province of Loja; and generate a proposal to include payment for environmental services, so that the autonomous governments of Province of Loja, to include in their development plans and land use. The research methodology was based on literature, history and social evidence. The methods used for selection were the first target of case studies, recopilón secondary information, generating information through interviews with key actors and implementation of assessment tools and systematization of results; while for the second objective methods were reviewing land use plans, information regarding the first goal with the second generation of conceptual guidelines, methodologies, techniques and institutional drafting a proposal to include payment of environmental services in the territorial development plans. As a result of the investigation a proposal that the autonomous governments of the province of Loja considered to update their development plans and territorial system and can incorporate the issue of incentives and payment for environmental services in their parishes, cantons and arises province Loja. In conclusion you can say that incentive schemes and / or payment for environmental services, should be viewed as a complementary management models of regional governments that have in their territory instrument. There is no single recipe or straitjacket for incentive schemes and / or payment for environmental services depends on each context and each of the conditions that are available so that it can be implemented; it should be clear that does not apply everywhere but where there are problems or threats to the conservation of ecological services. Finally, given the variety of factors involved in establishing incentive schemes and / or payment for environmental services, this proposal addresses the main aspects that should be incorporated.